“Espelho, espelho meu, existe alguém mais bela do que eu?”: um grupo focal de mulheres obesas com enfoque na psicologia analítica - Ferreira, Mariane Dias (2017)
In Brazil, according to the Ministry of Health in 2014, 50.8% of Brazilians were overweight, therefore, more than half of the population. Of these, 17.5% were obese, of which 54.7% were men and 47.4% were women. Obesity and overweight (which can lead to obesity) are disorders whose appearance and maintenance indicate the existence of several correlated factors, presenting, therefore, a multidimensional cause. Aside from health problems, being overweight also leads to a "negative view of the body," especially for women. This causes them to associate fitness with acceptance, social success and happiness. In general, studies on body image and self-esteem in obese women point to losses related to dissatisfaction, depreciation, distortion and concern with self-image in a way that is dissociated from the sense of identity. The present study sought to identify expectations of weight loss and examine body image and self-esteem through a focus group of six women between the ages of 36 and 50, who were overweight and obese, without distinguishing how much, through their narratives and the use of photographs. In the group narrative they tried to determine subjects related to body image, self-esteem and expectation of weight loss; such narrative was completed with a case study of each participant, in which the interlocution between symbols emerged from photos brought by each participant along with their personal narratives. The results indicated that, influenced by individual and collective factors, the participants experienced little expectation of weight loss along with the alienation of self-esteem which operated in the service of compensatory defenses. The functional aspects of the group, of the photographs and their clinical and symbolic potential within the framework of analytical psychology, enabled participants to reflect on their symptomatic and individual conditions by translating the conflict from measurement to mythical, or from number to narrative, so that they were able to initially reflect on individual demands and self-image rather than maintaining massive projections in the collective